Rocío Jurado, a very brief insurgent scene: write gestures so that the memory of an underground country comes to the surface and retouches its resistance - Trindade, Fabrício (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2024)
This article is a gesture written to make untold stories emerge, it is a dedication to artists, concert halls, and LGBTQIAPN+ saunas in Minas Gerais. After a 40-year career, in 2018, dragging performer José Alberto In Concert (1952-2023) achieved his youthful dream: to debut on a theater stage. Under the direction of Fabrício Trindade (1988-), Zé, at 66 years old, exposed himself by acting in the very brief insurgent scene Para Rocío Jurado.